Evaluation of Oil Resources Development Potential in the Arctic Region - Qing XU; Maixiu HU (Editorial Office of Ocean Development and Management, 2023)
With the increasingly fierce global energy competition, the Arctic, a "treasure land" of energy, has gradually become the focus of competition among countries. Based on the life cycle theory and the characteristics of the world oil market, this paper analyzed the theoretical basis of constructing the oil production equation of Arctic countries, and selected the multi-cycle Hubbert model and scenario analysis method to construct the oil production equation of Arctic countries. Moreover, based on the actual situation of theory and reality, different development scenarios were reasonably set up in order to analyze the impact of oil resources in the Arctic on the oil production of Arctic countries, and then studied the development potential of oil resources in the Arctic. The results showed that once the oil resources in the Arctic were developed, the peak oil of Arctic countries could be postponed for 2~4 years. The key development areas in the Arctic (West Siberia Basin, North Slope Basin of Alaska, Northwest Inland Basin and Sverdru Basin) had not been found, and the recoverable oil resources were richer. The effect of deferring the oil peak when developing the oil resources in this area was more obvious.